Implementasi Program Belajar Mandiri Dalam Meningkatkan Sikap Percaya Diri Siswa Di SMA Trensains Tebuireng Jombang - arif budiman; Ridlwan, Burhanuddin (PAI FAI UNHASY Tebuireng Jombang, 2024)
Independent learning is increasing willingness and learning skills in the learning process without involving other people and not depending on mentors, friends or other people. Self-confidence is an attitude or belief in one's own abilities, so that in taking action there is no doubt. This study discusses the implementation of independent learning programs in increasing students' self-confidence at Trensains Tebuireng High School, Jombang. The research focus is 1) How is the Independent Learning Program at Trensains Tebuireng Jombang High School? 2) What is the Confidence of Students at Trensains Tebuireng Jombang High School? 3) How is the Implementation of the Independent Learning Program in Increasing the Confidence of Students at Trensains Tebuireng Jombang High School?. This research uses a qualitative approach with a case study type of research. Data collection techniques in this study were carried out using interviews, observation and documentation. Informants in this study consisted of school principals, teachers and students. From the results of this study it can be concluded that 1) SMA Trensains Tebuireng Jombang encourages each student to have their own way of learning. 2) Confidence is a must for students. 3) The self-learning program in increasing self-confidence at Trensains Tebuireng Jombang Senior High School is carried out so that students can develop their potentials in their own way.